The area–heterogeneity tradeoff applied to spatial protection of rockfish (Sebastes spp.) species richness. Issue 6 (6th July 2018) - Frid, Alejandro; McGreer, Madeleine; Gale, Katie SP; Rubidge, Emily; Blaine, Tristan; Reid, Mike; Olson, Angeleen; Hankewich, Sandie; Mason, Ernest; Rolston, Dave; Tallio, Ernest
Abstract: The "area–heterogeneity tradeoff" hypothesis predicts unimodal effects of habitat heterogeneity on species richness, implying that habitats with intermediate heterogeneity may be priority for spatial protection. Alternatively, if heterogeneity effects are positive, then protecting the most heterogeneous habitats may take precedence. We tested for unimodal effects of habitat heterogeneity on the species density (area‐corrected richness) of rockfishes ( Sebastes spp.): long‐lived, benthic fishes vulnerable to overexploitation. Inconsistent with predictions, topographic structural complexity had a strong linear effect on species density; other heterogeneity measures had weaker, positive effects and the only unimodal effect (depth range) was weak. The clear implication is that, to protect the highest density of rockfish species, marine protected areas should include the most topographically complex substrates. Our results can also help refine and test species distribution models needed to inform spatial planning where in situ surveys are lacking. The area–heterogeneity tradeoff generates useful predictions for which support may be context‐dependent.